Effectiveness of heat-reflective asphalt pavements in mitigating urban heat islands: A systematic literature review - Tracy Leh Xin Wong; Ewe Loon Lim; Mohd Rosli Mohd Hasan; Oumar Orozi Sougui; Abdalrhman Milad; Xin Qu (Journal of Road Engineering)
Urban heat island (UHI) effect is a growing concern in numerous cities worldwide, which increases urban temperatures. Conventional asphalt pavements are a major contributor to the issue, causing environmental and health concerns. To tackle this issue, the implementation of cool pavements such as heat-reflective asphalt pavements has been introduced. This systematic literature review (SLR) thoroughly examines prior research to assess the effectiveness of heat-reflective asphalt pavements in reducing UHI effects. This SLR was conducted in accordance with the preferred reporting items for systematic review and meta-analysis (PRISMA) guidelines to enhance data reliability and minimize bias. This review process involved establishing review protocol, formulating review questions, systematically selecting articles through identification, screening, eligibility, quality appraisal, and data abstraction and analysis from various databases such as Scopus, Web of Science (WoS), Wiley, Taylor Francis, and ScienceDirect. Three primary themes and nine sub-themes were derived from the three review questions. From the results, heat-reflective asphalt pavements effectively minimized the UHI effect. However, their efficiency varies depending on factors such as pavement types, paving location, and use of cool materials. A comprehensive analysis examined heat-reflective pavement's mechanisms, benefits, and drawbacks. This investigation aimed to enhance comprehension and establish a robust basis for future studies in this field.